Dead man's island - Escott, John (Oxford University Press, 1991)
When someone has a secret and doesn't want other people to know about it, we say they have 'a skeleton in the cupboard'. Most people have a 'skeleton' and it follows her wherever goes. Her secret makes her more and more unhappy; slowly, but certainly, it is ruining her life. And then Carol meet someone with an even bigger secret. His secret is so big that he needs a whole island to hide it on. Perhaps Carol the best person to find out what his secret is. But if dhe does, what wil he do? Will he be pleased to share his secret, or will he be angry? It depends what his secret is. It all depends what kink of 'skeleton' he is hiding behind the locked-the locked door that Carol is going to open.